SISTEM PENGELOLAAN LINGKUNGAN SNI ISO 14001 DALAM PENGAWASAN KUALITAS (BAKU MUTU) AIR LIMBAH INDUSTRI DI PROVINSI RIAU - Refiano Andores (Pelantar Press, 2024)
The monitoring of the quality of industrial wastewater in Riau Province has been continuously carried out by the competent authorities. However, environmental conditions continue to deteriorate, especially environmental pollution caused by industrial wastewater. SNI ISO 14001 environmental management system is needed to support these activities. After researching, one of the causes that not many people know about is the competence of the laboratory for testing industrial wastewater samples. The report of test results issued by the laboratory is the key to determining the content of environmental pollutants, whether it exceeds the waste water quality standard or not. This condition determines whether the industry has violated the rules or not. Laboratory competence can be seen from the accreditation certificate owned by the laboratory. Accreditation is given by KAN (National Accreditation Committee). This research was conducted in October 2022, the results show that there are only less than 2% of testing laboratories in Riau Province from thousands of KAN accredited laboratories in Indonesia, only 0.71% of environmental laboratories can test wastewater. Distribution in regencies in Riau Province is also uneven, in Siak Regency 2 Labs, Bengkalis 3 Labs, Pekanbaru City 4 Labs, Rokan Hulu Regency, Rokan Hilir and Dumai City 1 each. Meanwhile, of the 13 regencies/cities in Riau Province, there are still 6 regencies, namely Indragiri Hulu, Kampar, Meranti Islands, Kuantan Singingi and Pelalawan which do not yet have a wastewater testing laboratory. This means that environmental laboratory facilities are still lacking in Riau Province and not available in several districts, and there are still many agencies that do not know that industrial wastewater testing must utilize the KAN-accredited environmental laboratory in monitoring the quality (quality standards) of industrial wastewater in Riau Province. Environmental laboratories should be able to develop, because there is economic potential from these testing services.